2019
DOI: 10.2174/1567202616666190206185133
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Cerebral Venous Sinus Stenosis Corrected by Stenting

Abstract: Background and Purpose: Cerebral Venous Sinus Stenosis (CVSS) usually results in severe Intracranial Hypertension (IH), which can be corrected by stenting immediately. However, there is a lack of evidence of the long-term good outcomes in patients with CVSS who underwent stenting. Methods: A total of 62 patients with imaging confirmed non-thrombotic and non-external compression CVSS were enrolled into this single center real-world cohort study after undergoing stenting, and were continuously followed up for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…), presented with very short segment of local stenosis in imaging, and tinnitus or idiopathic intracranial hypertension in clinical setting, which were corrected by stenting and obtained good outcomes. 22 However, whether the pathologic TS stenosis can affect the prognosis of ICH is still unclear, and our future study is still on going.…”
Section: Discussionmentioning
confidence: 94%
“…), presented with very short segment of local stenosis in imaging, and tinnitus or idiopathic intracranial hypertension in clinical setting, which were corrected by stenting and obtained good outcomes. 22 However, whether the pathologic TS stenosis can affect the prognosis of ICH is still unclear, and our future study is still on going.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we found that stenting could improve the anxiety and depression scores. Previous studies also showed that stent therapy could improve cerebral hypoperfusion and long-term outcomes in patients with CVSS or IJVS [ 41 , 42 , 43 ]. These findings may reveal an internal link between anxiety and depression symptoms, cloudy-like WMLs, and CVOD-mediated hypo-perfusion in patients with CVOD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that IIH involved more common in obese women and was poor response to medication treatment (3,4). However, increasing studies in recent years revealed that CVS stenosis might be one of the major etiologies of refractory IIH, and further, it is worth noting that cerebral sinus stenting can significantly reduce ICP and obtain relief of clinical symptoms accordingly (11)(12)(13). Therefore, CVS stenosis received increasing attention as a potential cause of IH (7,14).…”
Section: Cvs Stenosis and Idiopathic Intracranial Hypertension (Iih)mentioning
confidence: 99%